The exercise pressor reflex and active O(2) transport in peripheral arterial disease - Stavres, Jon (Physiol Rep, 2019)
It is unclear if the exaggerated exercise pressor reflex observed in peripheral arterial disease (PAD) patients facilitates Oxygen (O(2)) transport during presymptomatic exercise. Accordingly, this study compared O(2) transport between PAD patients and healthy controls during graded presymptomatic work. Seven PAD patients and seven healthy controls performed dynamic plantar flexion in the bore of a 3T MRI scanner. Perfusion, T(2)* (an index of relative tissue oxygenation), and SvO(2) (a measure of venous oxygen saturation) were collected from the medial gastrocnemius (MG) during the final 10 seconds of each stage. Blood pressure was also collected during the final minute of each stage. As expected, the pressor response to presymptomatic work (4 kg) was exaggerated in PAD patients compared to controls (+14 mmHg ± 4 and +7 mmHg ± 2, P ≤ 0.034). When normalized to changes in free water content (S(0)), T(2)* was lower at 2 kg in PAD patients compared to controls (−0.91 Δms/ΔAU ± 0.3 and 0.57 Δms/ΔAU ± 0.3, P ≤ 0.008); followed by a greater increase in perfusion at 4 kg in the PAD group (+18.8 mL/min/100g ± 6.2 vs. −0.21 mL/min/100g ± 3.2 in PAD and controls, P ≤ 0.026). Lastly, SvO(2) decreased at 4 kg in both groups (−13% ± 4 and −2% ± 4 in PAD and controls, P ≤ 0.049), suggesting an increase in O(2) extraction in the PAD group. Based on these findings, O(2) transport appears to be augmented during graded presymptomatic work in PAD patients, and this may be partially mediated by an exaggerated pressor response.